Sosialisasi Pelatihan Perawatan Service Gratis Sepeda Motor Roda Dua Di Kampung Sekban Kabupaten Fakfak - Rusdin, Rusdin; Imam Raharjo, Muh. (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
Fakfak Regency is an area located in the East Indonesia region of West Papua where the Regency has several villages and districts, especially the Sekban village, where this village is one of the regions that has a very fast motorcycle taxi base so this village is very appropriate to be made a PKM partner. Maintenance is an activity that is needed to maintain and restore the machine or work equipment to the best condition so that the machine can return to its original performance or return to standard. Motorcycles are two-wheeled vehicles where the vehicle is used as a transportation medium for motorcycle taxis by partners in Sekban Village and is also used as a medium for the implementation of the socialization of free service maintenance training by the PKM Polinef team